Socioeconomic and health correlates disability in India - Mishra, Radhe Shyam; Mohanthy, Sanjay K. (International Journal Of Community Medicine And Public Health, 2018)
Background: Disabled people suffered from multiple deprivations; poor health, low educational attainment, lower work participation and higher incidence of poverty. With demographic and epidemiological transition, the prevalence of disability also increases. This paper examines the socio economic and health correlates of disability in India. Methods: The unit data from District Level Household Survey (DLHS 4), is used in the analysis. Seven type of disability; namely, mental, visual, hearing, speech, locomotor, multiple, and any disability are analysed. Bi-variate and logistic regression analysis has been used to examine the association between disability and its socioeconomic, health covariates. Results: Prevalence of any disability was 2800 per 100,000 population in India. Prevalence of disability in non-empowered action group (EAG) states was highest for visual (800) followed by locomotor, hearing and mental. Age gradient of disability is quite strong; about 1140 person had any disability by age 10 compared to 3290 by age 40 years. Economic differentials in disability is large. Prevalence of any disability was 3680 among poorest wealth quintile compared to 2540 among richest. Conclusions: Disability was significantly higher in poor, less educated and older adults.